ANALISIS KEBUTUHAN PENGEMBANGAN ALAT BANTU PEMBELAJARAN INTERAKTIF BERBASIS KODULAR MATERI RANTAI MAKANAN UNTUK SISWA SEKOLAH DASAR - Dwicahya Suryadi, Made; Syahrial; Alirmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by science learning, specifically food chain material in elementary schools, which still faces challenges in the form of limited media and low student engagement. Teachers generally use lecture methods and conventional media, making learning monotonous and less interesting. The use of Android application-based digital media developed with the Kodular platform has been proven to increase motivation and learning outcomes. Before developing learning aids, a needs analysis is required to ensure the product's suitability with learning conditions in the field. This study aims to analyze the need for developing Kodular-based interactive learning aids on food chain material for fifth-grade elementary school students. The research uses a qualitative descriptive approach with data collection techniques through observation and interviews with teachers and students at SD Negeri 112/I Perumnas. The analysis results show that students need learning media that is interesting, interactive, and easy to understand, while teachers require practical and effective digital aids to explain abstract concepts visually. These findings form an important basis for developing Kodular-based interactive learning aids that align with the demands of the Merdeka Curriculum and the characteristics of elementary school students.